Fenomena Politik ‘Pamer-Ganti Bojo’ Konstelasi Pemilihan Bupati dan Wakil Bupati 2020 di Rembang - Sugihariyadi, Moh (POLITEA, 2020)
'Show-Changing Bojo' Politics in the Constellation of Election of Regent and Deputy Regent of Rembang. The election of the Regent and Deputy Regent of Rembang is based on the electeroral law. Electoral law is followed by an electoral process, one of which is by receiving input from the public. Because people have the right, opportunity and receive equal services based on statutory regulations. Submission of candidate pairs for Regent and Deputy Regent candidates by the DPC Political Party needs to consider the electoral law and electoral process, including ethical issues in politics. This study aims to analyze the political style of the candidates for regent and deputy regent of Rembang in leadership succession through the 'bojo showing off' model. The method used is qualitative with a phenomenological approach, which proves that community participation in the selection process of prospective regents and deputy regents at the level of political parties is never a concern. Therefore, 'showing off' bojo is one way to attract the attention of the public to pay attention to the succession of the leadership.